2019
DOI: 10.1038/s41598-019-52768-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxic Injuries of Rat’s Visceral Tissues Induced by Different Oximes

Abstract: Certain AChE reactivators, asoxime, obidoxime, K027, K048, and K075, when taken in overdoses and sometimes even when introduced within therapeutic ranges, may injure the different organs. As a continuation of previously published data, in this study, Wistar rats have sacrificed 24 hrs and 7 days after single im application of 0.1LD50, 0.5LD50 and 1.0LD50 of each reactivator, and examinated tissue samples were obtained for pathohistological and semiquantitative analysis. A severity of tissue alteration, express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…The whole visual field from each renal slice was analyzed and photographed at magnification 200×, by using a light microscope connected with a digital camera (BX-45, Olympus, Tokyo, Japan) for histopathological examination, as per our method previously published in the literature [42][43][44][45][46][47][48]. To assess the degree of renal damages, which consists of edema, hyperemia, neutrophils infiltration, glomerular cells' proliferation, and renal hemorrhages, a semi-quantitative 5-point scale was applied as previously described [43].…”
Section: Histopathological Examination and Semiquantitative Analysis Of Renal Damage Scorementioning
confidence: 99%
“…The whole visual field from each renal slice was analyzed and photographed at magnification 200×, by using a light microscope connected with a digital camera (BX-45, Olympus, Tokyo, Japan) for histopathological examination, as per our method previously published in the literature [42][43][44][45][46][47][48]. To assess the degree of renal damages, which consists of edema, hyperemia, neutrophils infiltration, glomerular cells' proliferation, and renal hemorrhages, a semi-quantitative 5-point scale was applied as previously described [43].…”
Section: Histopathological Examination and Semiquantitative Analysis Of Renal Damage Scorementioning
confidence: 99%
“…As found in the literature, it was confirmed that all reactivators tested at high dosages caused damage to both visceral tissues and the overall health of the individual. The data obtained may be an important support for dose choices regarding different reactivators structures for newly developed drugs [71,72].…”
Section: Ache Reactivation Processesmentioning
confidence: 84%
“…For detailed histopathological and semiquantitative analyses, Olympus BKS-43 (Olympus Europa, Hamburg, Germany) with a digital camera and Cell D software (Olympus, Munster, Germany) were used. Complete analyses were performed by pathologists blind of the treatment groups as per our method previously published in the literature [ 20 , 21 , 22 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…The intensity of inflammatory injury of the lungs was scored and counted in 30 tissue slices per group (i.e., five tissues from each experimental group and six slices from each tissue) with a magnification of 200×, in accordance with previously published literature [ 20 , 21 , 22 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The severity grades were expressed as a pulmonary damage score (PDS), quantified, and precisely calculated.…”
Section: Methodsmentioning
confidence: 99%